Knowledge connectedness within and across home country borders: Spatial heterogeneity and the technological scope of firm innovations - Scalera, Vittoria G.; Perri, Alessandra; Hannigan, T. J. (Journal of International Business Studies, 2018)
We explore how knowledge-based connections to domestic and foreign locations affect the technological scope of firm innovations. Inspired by a blend of Economic Geography and International Business perspectives, we propose a theoretical framework that distinguishes between domestic subnational differences and cross-national spatial heterogeneity. Further, we combine the Penrosean view of managerial capabilities with the attention-based theory of the firm. Analyzing a sample of US-based firms between 1990 and 2006, we show that both domestic and international knowledge connectedness affect the technological scope of firm innovations, but their effects are different. The breadth of international knowledge connectedness appears to be positively associated with the technological scope of firm innovations. However, the breadth of domestic knowledge connectedness positively contributes to the technological scope of firm innovations up to a certain point, beyond which the bounded rationality of managers constrains firms’ ability to further leverage subnational heterogeneity. Thus, domestic search is more likely to be challenged by limited managerial bandwidth. Lastly, domestic and international knowledge connectedness significantly interact with each other to explain the technological scope of firm innovations.